Tracheobronchial amyloidosis: an uncommon disease with a common presentation. Issue 7 (2nd August 2020) - Mangla, Loveleen; Vadala, Rohit; Kadli, Shirish Kumar; Prajapat, Deepak; Talwar, Deepak
Abstract: Amyloidosis is an uncommon heterogeneous and multi‐systemic disease characterized by extracellular amyloid deposition. The size of proteins varies and forms a part of local disease or systemic process. Light chain amyloidosis (AL) is the most prevalent form of systemic amyloidosis which may also be seen in localized disease. Isolated tracheobronchial amyloidosis (TBA) is rather unusual with local amyloid deposition which may pose a diagnostic dilemma with subsequent therapeutic challenge. Awareness of such a presentation is crucial in the diagnosis of this rare disease. We describe three cases who presented with haemoptysis, which on further evaluation were diagnosed as isolated TBA, and a review of literature. Abstract : We describe three cases who presented with haemoptysis, which on further evaluation were diagnosed as isolated tracheobronchial amyloidosis, and a review of literature.